Antiviral resistance in influenza viruses: Resistance to antiviral in influenza viruses - Márquez Domínguez, Luis; Márquez Matla, Kevin; Reyes Leyva, Julio; Vallejo Ruíz, Verónica; Santos López, Gerardo (Cellular and Molecular Biology, 2023)
Influenza represents a major threat to public health worldwide, vaccination is the most effective strategy to reduce infections. However, achieving adequate vaccination rates is challenging and vaccination does not always guarantee complete protection. For this reason, antiviral drugs represent an important measure to reduce the risk of complications in high-risk patients. However, influenza viruses have a high mutation rate which causes genetic, biochemical, and pathogenic changes that represent a challenge both for the constant replacement of vaccines and reduce their susceptibility to antiviral action. This makes it necessary to determine the mechanisms of these processes, as well as their epidemiological surveillance and, of course, the development of new therapeutic options that may be available in the event of a widespread resistance phenomenon. In this article we review some of the relevant aspects of the replicative cycle of influenza viruses, the antivirals currently used, as well as their resistance mechanisms.